(untitled) (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
Learning English in higher education involves more than just mastering vocabulary and grammar; it is deeply influenced by various psychological factors. These include motivation, anxiety, self-confidence, and attitudes toward the language. Students who lack confidence or experience high levels of anxiety may struggle to participate actively in lessons or retain information. Conversely, those with strong internal motivation and positive learner beliefs often perform better. Understanding and addressing these psychological aspects can significantly improve teaching outcomes. This paper explores how such factors influence English language acquisition and suggests ways to create a supportive learning environment in higher education.